EVALUASI PEMBELAJARAN ONLINE DENGAN GOOGLE FORM - Yusra; Supratman Zakir (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Abstrak. At the end of 2019, an epidemic hit the international world, including Indonesia. This outbreak is known as Coronavirus Disease 2019 (Covid-19), where it spreads very quickly and confirmed patients continue to increase every day. So this condition has quite a significant impact on all sectors of life, be it social, religious, educational, economic, and so on. In the field of education itself, there are fundamental changes in the learning system. Where the teaching and learning process is usually carried out face-to-face, now it must be shifted to online learning. The aim of writing this article is to examine the online learning evaluation system using Google Forms. Therefore, we must know the online learning evaluation system using Google Forms. In this article the author uses the library research method, namely deepening, examining and identifying knowledge contained in the literature (reading sources, reference books or other research results). The results of this research show an evaluation of online learning using Google Form.